2017
DOI: 10.1089/ten.tea.2017.0102
|View full text |Cite
|
Sign up to set email alerts
|

Matrix-Bound Nanovesicles Recapitulate Extracellular Matrix Effects on Macrophage Phenotype

Abstract: The early macrophage response to biomaterials has been shown to be a critical and predictive determinant of downstream outcomes. When properly prepared, bioscaffolds composed of mammalian extracellular matrix (ECM) have been shown to promote a transition in macrophage behavior from a proinflammatory to a regulatory/anti-inflammatory phenotype, which in turn has been associated with constructive and functional tissue repair. The mechanism by which ECM bioscaffolds promote this phenotypic transition, however, is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
81
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(84 citation statements)
references
References 62 publications
3
81
0
Order By: Relevance
“…Application of the SIS hydrogel showed restoration of colonic epithelial barrier function and mitigation of the proinflammatory macrophage phenotype. Overall, results from this study, and others, 33 , 80 , 137 , 138 , 139 have shown that ECM possesses immunomodulatory properties, a process shown to be a critical determinant of downstream constructive and functional tissue-remodeling outcomes.…”
Section: Gi Tissue Engineeringsupporting
confidence: 70%
See 2 more Smart Citations
“…Application of the SIS hydrogel showed restoration of colonic epithelial barrier function and mitigation of the proinflammatory macrophage phenotype. Overall, results from this study, and others, 33 , 80 , 137 , 138 , 139 have shown that ECM possesses immunomodulatory properties, a process shown to be a critical determinant of downstream constructive and functional tissue-remodeling outcomes.…”
Section: Gi Tissue Engineeringsupporting
confidence: 70%
“… 69 , 70 , 71 , 72 Additional degradation products of ECM bioscaffolds include growth factors stored within the matrix 73 , 74 , 75 , 76 ; structural molecules such as collagen, 9 , 77 laminin, 77 fibronectin, 78 and glycosaminoglycans 79 ; and matrix-bound nanovesicles (MBV), nanometer-sized membranous vesicles that are similar in size and structure to exosomes. 80 , 81 Although exosomes exist exclusively in body fluids, MBV are bound within the collagen network of the ECM. 81 MBV were shown to be sufficient (ie, in an ECM-independent manner) to recapitulate phenotypical and functional effects attributed to ECM bioscaffolds, as assessed by in vitro cell culture studies.…”
Section: Ecm Bioscaffold Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…The immunomodulatory effect of decellularized ECM (dECM) mainly depends on scaffold structure and composition. Huleihel and colleagues, for example, recently demonstrated that matrix-bound vesicles (MBVs) present in urinary bladder matrix are responsible for macrophage polarization towards the anti-inflammatory phenotype, via three miRs (miR125b-5p, miR143-3p, and miR145-5p) carried within the vesicles [ 26 ]. The authors hypothesized that, during degradation of the ECM-based scaffold, the released MBVs are internalized by macrophages, eliciting their polarization.…”
Section: Immunomodulation By Implanted Scaffoldsmentioning
confidence: 99%
“…It is also known that physiologically native EVs actively interact with the ECM (Buzas et al, 2018 ) and the EV-ECM complexes are mediating significant biological functions of both ECMs and EVs (Sung et al, 2015 ). Recently, matrix-bound vesicles (MBVs) are identified to play a significant role in mediating the regenerative functions of ECM scaffolds (Huleihel et al, 2016 , 2017 ; van der Merwe et al, 2017 ; Rilla et al, 2019 ), which highlights the biological functions of the EV-ECM structural complexes. Therefore, designing and constructing biomaterial scaffolds to mimic the structure of the EV-ECM complex and the physiological interactions between the ECM and EVs, represents an attractive and promising novel approach for tissue engineering applications.…”
Section: Introductionmentioning
confidence: 99%